68=p-26

Simple and best practice solution for 68=p-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 68=p-26 equation:



68=p-26
We move all terms to the left:
68-(p-26)=0
We get rid of parentheses
-p+26+68=0
We add all the numbers together, and all the variables
-1p+94=0
We move all terms containing p to the left, all other terms to the right
-p=-94
p=-94/-1
p=+94

See similar equations:

| 3(t+8)=25.5 | | -6b-6.75-7.1b=1.5b-2.35 | | 10m^2-20m+40=-8 | | -m-3+1=-7-2m | | -56x^2-15x-1=0 | | 10x+10(x-4)=1,000 | | 0.08(x-2000)+3000=x | | x^2+25=-4x | | -y-12/5=3 | | 6-6x=7x-9x—4 | | 3a+(5a-8)+(3a+14)=180 | | x+7.3=12.5 | | b+2/3=4 | | (4x7)=(2x-1) | | 3+7z=-z+6z-15 | | 18+12x=-54 | | -118=9x+1 | | x+4=6+3x–10x | | 3(-10x+50)=69 | | x/11-2=-8 | | –y–125=3 | | (x+7)/4=-12 | | t(-13)=28 | | -2.5x+3.8=-2x–4.3 | | 74=-7a+4 | | 6(n-77)=96 | | 5-n=18 | | 10-s=-8+8s | | 3x²=588 | | –m−3+1=–7−2m | | 7/2x+1/2x=1,1/2+5/2x | | d-433=-266 |

Equations solver categories